(untitled) (Dhaka University Journal of Biological Sciences, 2011)
Key words: Arbuscular mycorrhizal fungi; Karnajhora Rubber Estate; Phosphorus; Pueraria; Upland DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8882 Dhaka Univ. J. Biol. Sci. 20(1): 99-102, 2011 (January)